{4-Chloro-2′-[1-(5-chloro-2-oxidophenyl)-ethylidene- κ3O,N2′ ,O′]benzhydrazido}-tris(pyridine- κN)nickel(II) pyridine solvate - Ali, Hapipah Mohd; Yamin, B.M.; Basirun, Wan Jefrey; Khamis, N.A. (International Union of Crystallography, 2004)
The crystal structure of the title compound, [Ni(C15H 10Cl2-N2O2)(C5H 5N)3]·C5H5N, is built of molecules of a mononuclear nickel complex and uncoordinated solvent pyridine molecules. The NiII atom in the complex is coordinated by two O and one N atoms of the meridional tridentate ligand, viz. the twice deprotonated hydrazone formed from 2-hydroxy-5-chloroacetophenone and p-chlorobenzhydrazide. The remaining three coordination sites of the Ni octahedron are occupied by three coordinated pyridine ligands. © 2004 International Union of Crystallography Prinled in Great Britain - all rights reserved.